The Ecology of Zaprionus Genus in Brazil and Adaptation Process during The Bioinvasion - Galego, Luis Gustavo da Conceicao (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
The Ecology of Zaprionus Genus in Brazil and Adaptation Process during The Bioinvasion